2009
DOI: 10.1021/jf902046s
|View full text |Cite
|
Sign up to set email alerts
|

Red Mold Rice Promoted Antioxidase Activity against Oxidative Injury and Improved the Memory Ability of Zinc-Deficient Rats

Abstract: Zn deficiency is a common disease leading to memory impairment with increasing age. This study evaluated the protection effects of red mold rice (RMR) administration and Zn supplementation against memory and learning ability impairments from oxidative stress caused by Zn deficiency. Rats (4 weeks old) were induced to be Zn deficiency by a Zn-deficient diet for 12 weeks. After that, rats were administered Zn, 1xRMR, 5xRMR, and various dosages of RMR plus Zn, respectively. Decreases of antioxidant enzyme activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The passive avoidance task was carried out from day 29 to day 31 according to Lee et al The apparatus consisted of light and dark chambers. A door was set for separation of the two chambers.…”
Section: Methodsmentioning
confidence: 99%
“…The passive avoidance task was carried out from day 29 to day 31 according to Lee et al The apparatus consisted of light and dark chambers. A door was set for separation of the two chambers.…”
Section: Methodsmentioning
confidence: 99%
“…In this assay, 100  μ L of homogenates reacted with 10 mg/mL of NBT and measured by the absorbance at 570 nm [21]. …”
Section: Methodsmentioning
confidence: 99%
“…A further study reported that RMR extract treatment suppressed cholesterol-raised β-secretase activity and increased the neuroprotective soluble amyloid precursor protein (APP) R-fragment secretion in vitro and in vivo (33). Other studies revealed that RMR administration has a protective effect in a Zn-deficiency model (36) and Parkinson’s disease model (37). The administration of RMR significantly ameliorated behavioral dysfunction and improved the activity of antioxidant enzymes including glutathione reductase, glutathione peroxidase, SOD, and catalase, which all lead to markedly reduced reactive oxygen species (ROS) production.…”
Section: The Effects Of Fermented Foods On Cognitive Functionmentioning
confidence: 99%